Comparative study of intralesional injection of triamcinolone versus placental extract in cases of oral submucous fibrosis - Dhanani, Ankur N.; Patel, Alpesh V.; Laungani, Vijay S.; Patel, Margi H.; Sharma, Pooja A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Oral submucous fibrosis (OSMF) is a common premalignant condition caused by chewing arecanut, betel quid and gutkha with tobacco. One of the important therapeutic modalities is intralesional injection therapy. The most commonly used intralesional agents are placental extract, corticosteroids and hyaluronidase. Methods: Patients of OSMF (30) were randomly allocated and 15 patients were given 1 ml placental extract submucosally in each retromolar trigon weekly for 8 weeks and 15 patients were injected with 40 mg/ml of triamcinolone submucosally on each side weekly for 8 weeks. The mouth opening was measured as the inter-incisor distance by Vernier calliper at maximal active mouth opening by patient at initial visit and every follow up visit and recorded. Treatment outcome was evaluated on the basis of improvement in trismus, oral mucosal pattern and reduction in burning sensation. Results: Out of 30 patients, 27 were males and 3 females. 16 patients (53.33%) were in the age group of 21-30 years. Most of patients in our study had complain of reduced mouth opening and inability to take spicy food which is 93.33% of cases followed by burning sensation in mouth 90%, oral ulceration 83.33%, dryness of mouth 30%, difficulty/pain in swallowing 13.33% and halitosis 2%. 60% of patients mouth opening was improved >10 mm with triamcinolone while in placental extract 26.6%. Symptomatic relief were obtained more with injection placental extract. Conclusions: Triamcinolone injection has more improvement in mouth opening compared to placental extract. It was observed that injection placental extract gives good symptomatic relief in the major symptoms like burning sensation in mouth, inability to take spicy food, oral ulceration compared to injection triamcinolone.